PENGARUH BRAND ACTIVATION PIZZA HUT INDONESIA DI MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN PADA PRODUK LIMO PIZZA - Elfariany, Zorna (Universitas Negeri Surabaya, 2023)
This research aims to determine the influence of Pizza Hut Indonesia's brand activation on Instagram on consumer buying interest in the product Limo Pizza, as well as the extent of the influence it exerts. The researchers focused on the marketing communication activity strategy of brand activation, specifically utilizing social media and adopted by Pizza Hut Indonesia for the promotion of Limo Pizza. The population of this study consists of followers of the Instagram account @pizzahut.indonesia, and the sample size was determined to be 100 individuals using the Lemeshow formula. The researchers analyzed the data using simple linear regression with the assistance of SPSS version 25. The results of the study showed that Pizza Hut Indonesia's brand activation on Instagram has a significant influence on consumer buying interest in Limo Pizza, as indicated by the t-test and F-test values being less than 0.050, leading to the acceptance of the hypothesis. Through the coefficient of determination test, the researchers found that the influence of Pizza Hut Indonesia's brand activation on Instagram on consumer buying interest in Limo Pizza amounts to 48.3%. In conclusion, the research findings demonstrate that brand activation on Pizza Hut Indonesia's Instagram has a significant impact on consumer interest in purchasing Limo Pizza, accounting for 48.3% of the variation in buying interest.